The role of melano‐macrophage aggregates in the storage of mercury and other metals: An example from yelloweye rockfish (Sebastes ruberrimus). (14th July 2015) - Barst, Benjamin D.; Bridges, Kristin; Korbas, Malgorzata; Roberts, Aaron P.; Van Kirk, Kray; McNeel, Kevin; Drevnick, Paul E.
Abstract: Melano‐macrophage aggregates, collections of specialized cells of the innate immune system of fish, are considered a general biomarker for contaminant toxicity. To elucidate further the relationship between macrophage aggregates and metals exposure, yelloweye rockfish ( Sebastes ruberrimus ), a long‐lived species, were sampled from the east and west coasts of Prince of Wales Island, Alaska. Metals concentrations in livers (inorganic Hg, methyl mercury, Se, Ni, Cd, Cu, Zn) and spleens (inorganic Hg and methyl mercury) were determined, as well as their correlations with melano‐macrophage aggregate area. Sections of liver tissue were analyzed by laser ablation‐inductively coupled plasma–mass spectrometry to determine how metals were spatially distributed between hepatocytes and macrophage aggregates. The concentration of inorganic Hg in whole tissue was the best predictor of macrophage area in yelloweye livers and spleens. Macrophage aggregates had higher relative concentrations than most metals compared with the surrounding hepatocytes. However, not all metals were accumulated to the same degree, as evidenced by differences in the ratios of metals in macrophages compared with hepatocytes. Laser ablation data were corroborated with the results of X‐ray synchrotron fluorescence imaging of a yelloweye liver section. Hepatic macrophage aggregates in yelloweye rockfish may play an important role in the detoxification and storage of Hg and other metals. Environ Toxicol Chem 2015;34:1918–1925. © 2015 SETAC